Transforming Tomaszów Mazowiecki Towards a Modern City: Summarizing a Three-Decade of Post-Socialist Urban Transition - Waldemar CUDNY (Communications of International Proceedings, 2024)
The aim of this study is to summarize thirty years of demographic and socio-economic transformations in Tomaszów Mazowiecki, a medium-sized post-industrial Polish city. Although there has been extensive research on the issue of post-socialist transition in fields such as economy, sociology, and human geography, there is a lack of comprehensive summaries. This text seeks to fill that gap by presenting an overview of thirty years of post-socialist transition using Tomaszów Mazowiecki as an example. The analysis is based on desk research, which includes reviewing literature and statistical data. The post-socialist transition in Tomaszów Mazowiecki has been characterized by significant socio-economic changes, such as the decline of industrial giants, the growth of a diverse service sector, and integration into broader European socio-economic frameworks following the fall of communism. Like many post-socialist cities, Tomaszów Mazowiecki has experienced periods of profound change, including industrial diversification, demographic shifts, and social challenges. However, it has ultimately emerged as a city that balances modernization with sustainable development and economic growth with quality of life.
Keywords: Post-socialist cities; post-socialist transition; urban change; Tomaszów Mazowiecki; Poland.